Labor Supply at the Extensive and Intensive Margins: The EITC, Welfare, and Hours Worked - Meyer, Bruce D (American Economic Review, 2002)
Some previous studies have emphasized differences between labor-supply responses on the extensive margin (participation) and intensive margin (hours worked) (e.g., James J. Heckman, 1993; Jean Kimmel and Thomas J. Kniesner, 1998). Recent tax and welfare policy changes provide a potentially more convincing way of identifying these responses than is available in other nonexperimental data. The Earned Income Tax Credit (EITC) changes during the 1990– 1996 period sharply altered the budget sets of single mothers over a short period of time. These changes in incentives are likely to be unrelated to differences across individuals in the desire to work and thus are likely to be exogenous to labor-supply decisions. This lack of exogeneity is harder to claim for wage differences across people, which are the main alternative source of identifying variation. In addition to preference heterogeneity, wages are driven by supply and demand factors that one must account for to obtain valid estimates using wage variation. The EITC unequivocally encourages single parents to work at least some hours during a year because it shifts out the budget set at all positive hours points. This first prediction is clearly confirmed by the data. In addition, theory implies that the EITC will decrease hours worked among those already working because most recipients are on the plateau or phase-out portions of the credit schedule. For these recipients, the EITC reduces or does not affect the after-tax wage while at the same time discouraging work through the income effect of the credit payment. However, recent hours-worked patterns for EITC-eligible individuals do not appear to fit this second prediction. Hours and weeks worked by likely recipient groups have not fallen. This paper analyzes this puzzling finding, building on earlier work by Nada Eissa and Jeffrey Liebman (1996) and Meyer and Dan T. Rosenbaum (1999). This study shows that nearly all of the laborsupply adjustment of single mothers occurs at the extensive margin, not the intensive margin. This finding raises the issue of what model features are needed to explain both participation and hours but leaves the answer to be provided in future work. This finding also suggests that the large literature simulating alternative policies for low-wage workers such as the EITC may be misleading because nearly all work has used models that imply similar responses on participation and hours margins.